Sub‐Nanometer Thick Gold Nanosheets as Highly Efficient Catalysts. Issue 21 (6th August 2019) - Ye, Sunjie; Brown, Andy P.; Stammers, Ashley C.; Thomson, Neil H.; Wen, Jin; Roach, Lucien; Bushby, Richard J.; Coletta, Patricia Louise; Critchley, Kevin; Connell, Simon D.; Markham, Alexander F.; Brydson, Rik; et al.
Abstract: 2D metal nanomaterials offer exciting prospects in terms of their properties and functions. However, the ambient aqueous synthesis of atomically‐thin, 2D metallic nanomaterials represents a significant challenge. Herein, freestanding and atomically‐thin gold nanosheets with a thickness of only 0.47 nm (two atomic layers thick) are synthesized via a one‐step aqueous approach at 20 °C, using methyl orange as a confining agent. Owing to the high surface‐area‐to‐volume ratio, abundance of unsaturated atoms exposed on the surface and large interfacial areas arising from their ultrathin 2D nature, the as‐prepared Au nanosheets demonstrate excellent catalysis performance in the model reaction of 4‐nitrophenol reduction, and remarkable peroxidase‐mimicking activity, which enables a highly sensitive colorimetric sensing of H2 O2 with a detection limit of 0.11 × 10 −6 m . This work represents the first fabrication of freestanding 2D gold with a sub‐nanometer thickness, opens up an innovative pathway toward atomically‐thin metal nanomaterials that can serve as model systems for inspiring fundamental advances in materials science, and holds potential across a wide region of applications. Abstract : Sub‐nanometer gold nanosheets (thickness: 0.47 ± 0.01 nm) are successfully prepared via a facile aqueous synthesis at an ambient temperature. These nanosheets represent the first free‐standing 2D gold nanostructure with a sub‐nanometer thickness, and demonstrate excellent catalysis performance in the model reaction of 4‐nitrophenol reduction, coupled with remarkable peroxidase‐mimicking activity, which enables a highly sensitive colorimetric detection of H2 O2 .